Assessment of Training Needs for Improving Professional Competencies of Extension functionaries - Slathia, P.S.; Narinder, P.; Bhagat, G.R.; Kher, S.K. (Indian Journal of Extension Education, 2009)
A vast pool of extension workers engaged in the technology dissemination needs their knowledge and skill to be periodically updated so as to keep abreast of latest technology and modes of their dissemination in the fastly changing global and national scenario. Present research was carried out to assess the training needs of extension functionaries of state line development working in the Jammu and Kashmir State. The study sample consisted of 150 respondents . It was found that majority of the field functionaries lacked the requisite skills of the latest extension techniques regarding technology transfer. The functionaries of agricultural department needed training in diversified agricultural approaches in which wide knowledge and skill gaps were observed . Likewise respondents from animal husbandry department needed trainings in latest pharmacological development . Functionaries from department of horticulture, forestry and rural development lacked required human relation skills , which need to be updated for improving the professional competencies of the functionaries. It is, therefore, suggested to prepare the training modules best suited to the needs of the extension functionaries of the state line departments and implementation of it by the concerned training institutes.